Global progress and prospects of triclosan and triclocarban research in the environmental field: a bibliometric analysis and review - Han, Jie; Chen, Hui; Ren, Zhe; Zhang, Xue; Shao, Zixuan; Wei, Qiuhua; Li, Zhonghong (Frontiers in Environmental Science, 2025)
The widespread application of triclosan (TCS) and triclocarban (TCC) as antimicrobial agents has raised significant concerns among environmental scientists about their environmental behavior, ecological effects, and possible human health risks. To comprehensively understand the current research landscape and developmental trends pertaining to TCS and TCC research in the environmental field, this study analyzed literature data from the Web of Science Core Collection (WOSCC) database from 2002 to 2024 using advanced visualization tools such as Bibliometrix, VOSviewer, and Citespace. The study revealed that China dominates the field of TCS and TCC in environmental research with a publication count significantly higher than other countries, while Brazil and India, as developing nations, also make substantial contributions, ranking among the top 10 in publication output. The journals Science of the Total Environment, Chemosphere, and Environmental Science and Technology featured the highest number of publications on this topic. Keywords co-occurrence and burst anlaysis revealed that contemporary research predominantly concentrates on the environmental behaviour and fate of these compounds, as well as their ecotoxicological impacts and mechanisms. Additionally, there is a focused interest in evaluating human exposure risks and investigating technologies for their degradation and removal. The interaction of these compounds with other environmental pollutants, along with their mechanisms, and the improvement of removal and degradation technologies, are expected to be key focal points in forthcoming research efforts. Based on the comprehensive bibliometric analysis, this study highlights the critical need for environmental policies to address the persistence and bioaccumulation potential of TCS and TCC, urging the development of more effective degradation technologies and strategies to mitigate their environmental and health impacts, which could guide future research and regulatory frameworks.